Spatiotemporal magnetic fields enhance cytosolic Ca2+ levels and induce actin polymerization via activation of voltage-gated sodium channels in skeletal muscle cells - Rubio Ayala, Mónica; Syrovets, Tatiana; Hafner, Susanne; Zablotskii, Vitalii; Dejneka, Alexandr; Simmet, Thomas (Biomaterials, 2018)
Cellular function is modulated by the electric membrane potential controlling intracellular physiology and signal propagation from a motor neuron to a muscle fiber resulting in muscle contraction. Unlike electric fields, magnetic fields are not attenuated by biological materials and penetrate deep into the tissue. We used complex spatiotemporal magnetic fields (17-70 mT) to control intracellular signaling in skeletal muscle cells. By changing different parameters of the alternating magnetic field (amplitude, inversion time, rotation frequency), we induced transient depolarization of cellular membranes leading to i) Na+ influx through voltage-gated sodium channels (VGSC), ii) cytosolic calcium increase, and iii) VGSC- and ryanodine receptor-dependent increase of actin polymerization. The ion fluxes occurred only, when the field was applied and returned to baseline after the field was turned off. The 30-s-activation-cycle could be repeated without any loss of signal intensity. By contrast, static magnetic fields of the same strength exhibited no effect on myotube Ca2+ levels. Mathematical modeling suggested a role for the alternating magnetic field-induced eddy current, which mediates a local change in the membrane potential triggering the activation of VGSC. These findings might pave the way for the use of complex magnetic fields to improve function of skeletal muscles in myopathies.
Keywords: Eddy current; Magnetic Fields; membránové potenciály; Skeletal muscle; buněčné linie; Modeling; Cell Membrane; myoblasty; Models, Biological; gating iontového kanálu; Polymerization; Ion Channel Gating; sodíkové kanálky řízené napětím; Membrane Potentials; Cell Line; Calcium; Cell Survival; vápníková signalizace; Voltage-Gated Sodium Channels; myši; Mice; aktiny; Actins; vápník; viabilita buněk; biologické modely; magnetické pole; zvířata; kosterní svalová vlákna; buněčná membrána; Cytosolic calcium; Animals; polymerizace; Muscle Fibers, Skeletal; Voltage-gated sodium channels; Myoblasts; Calcium Signaling; Alternating magnetic field